The impacts of climate-smart agricultural practices on household income and food security: evidence from Doyogena and Basona climate-smart landscapes - Tesfaye, Abonesh; Hammond, James; Radeny, Maren A.O.; Recha, John W.M.; Nigussie, Abebe; Ambaw, Gebermedihin; Wijk, Mark T. van; Tamene, Lulseged D.; Abera, Wuletawu; Solomon, Dawit (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The aim of this paper is to assess the impacts of CSA practices on household income and food security in Ethiopia. Data was collected from 796 randomly selected smallholder farmers from the two climate-smart villages of Doyogena (399) and Basona (397) districts. Half of the selected farmers were implementing CSA practices, while the remaining half were farmers who were not implementing CSA practices. Using a propensity score matching approach, the paper examined the contribution of CSA practices on farm household income and food security. The estimated results show that the adoption of CSA practices has enhanced household food security in Doyogena, whereas, in Basona, the implementation of CSA practices improved the average annual income of households. This study suggests that introducing CSA practices and scaling up of these practices should be site-specific but not be a one-size-fits-all approach. Promoting and scaling up of these practices may require assessing the needs and priorities of communities living in different locations.